The effect of willow control using a glyphosate formulation on aquatic invertebrates within a New Zealand wetland. Issue 1 (2nd January 2018) - Wech, Janine; Suren, Alastair; Brady, Matthew; Kilroy, Cathy
ABSTRACT: Exotic trees, such as willow ( Salix spp.), have become invasive around New Zealand waterways. Lowland wetlands in particular are vulnerable, with invasions changing hydrology and causing biodiversity loss. Applying herbicide to the willow canopy is a cost-effective control method, however uncertainty remains around effects on wetland aquatic invertebrates. Within a North Island, New Zealand, wetland, we conducted a paired before-after, control-impact study to determine if aerially applied glyphosate (with adjuvants) affected invertebrate assemblages. No effect on communities was detected during the first year after glyphosate treatment, however significant differences between control and spray-exposed communities were found during the second year, coinciding with a significant drought event in March 2013. By the third year, no statistically significant differences were found between communities from control and spray-exposed sites. This study suggests that glyphosate use, in comparable environments, is unlikely to affect aquatic invertebrates. Furthermore, the study illustrates invertebrate communities' resilience to drought events.